Perbandingan Waktu Capaian Tes Motorik Menggunakan Spinal Needle No. 25 dan No. 27g Pada Pasien Sectio Caesaria Dengan Spinal Anestesi di RSUD Sambas - A, Anggiatwan; Handayani, Rahmaya Nova; Suryani, Roro Lintang (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Spinal anesthesia is the most widely chosen anesthesia technique and is performed in lower extremity, anorectal, urology, obstetrics and gynecology, and lower abdominal surgery. This procedure is chosen by anesthesiologists and patients because it has the advantage of being able to provide anesthesia and analgesia effects together, prevent serious respiratory complications from general anesthesia, and a high level of patient satisfaction (Dwiputra, 2023). General Objective To determine the comparison of the timing of the motor test using spinal needle number 25 and number 27G in Sectio Caesaria patients with spinal anesthesia. This research is included in Quantitative research. The type of research used is observational analysis with a Cross Sectional approach. The number of samples was enlisted from two groups where respondents using a 25G spinal needle consisted of 85 respondents and respondents who used a 27G spinal needle consisted of 85 respondents. Based on the results obtained from the 2 sample groups used, in the sample of respondents who were carried out spinal anesthesia using a 25 G needle, the motor achievement time was 3.44 minutes and in the sample of respondents who were carried out spinal anesthesia using a 27 G needle for 3.10 minutes. Results Difference in the time of achievement of motor tests using spinal needle no. 25 and no. 27G in patients with sectio caesarean section with spinal anesthesia with the analysis test The data used in this study was a data test with Man-Whitney where the results in the data test stated a Sig value of 0.001 which means a sig value of <0.05 so it can be concluded that there is a significant difference between the two groups.